Development Of Learning Media Assisted By Capcut Theme 2 Subtema 1 Learning 6 In Class II Elementary School - Diah Aulia Azizatur Rohmah; Shirly Rizki Kusumaningrum; Radeni Sukma Indra Dewi (Unversitas Muhammadiyah Mataram, 2022)
Abstract: The purpose of this study is to develop capcut-assisted learning media on theme 2 sub-theme 1 learning 6 in grade II elementary school that is valid, practical, interesting and effective. Valid according to material expert (Dra. Widayati M.H), media expert (Ferril Irham Muzaki S.Pd., M.Pd) and user/teacher (Luluk Muthori'ah, S.Pd) while practical, interesting and effective according to grade II students SDN Kauman 2 Blitar City. The research method uses R&D development according to Borg & Gall. The stages in this research include: 1) potential and problems, 2) data collection, 3) product design, 4) product validation, 5) product revision, 6) product trial, 7) product revision, 8) usage trial 9) product revision. The data collection instruments used were interview guidelines, validation instruments, and student questionnaires. The type of data in the form of quantitative data is obtained from the results of the material validator questionnaire, media, users/teachers, and students. Qualitative data obtained from suggestions and input from experts, users and students. The validator analysis technique uses a Likert Scale. While the data obtained from product trials and usage trials using the Guttman scale. The results of material validation are 100% (very valid), media validation is 93.75% (very valid), user validation is 100% (very valid), and product testing is 98.8% (very practical/interesting). So it can be concluded that the capcut-assisted learning media is stated to be very valid, practical, interesting and effective to use in learning theme 2 sub-theme 1 learning 6.Abstrak: Tujuan pada penelitian ini mengembangkan media pembelajaran berbantuan capcut pada tema 2 subtema 1 pembelajaran 6 di kelas II sekolah dasar yang valid, praktis, menarik dan efektif. Valid menurut ahli materi (Dra. Widayati M.H), ahli media (Ferril Irham Muzaki S.Pd.,M.Pd) dan pengguna/guru (Luluk Muthori’ah, S.Pd) sedangkan praktis, menarik dan efektif menurut siswa kelas II SDN Kauman 2 Kota Blitar. Metode penelitian menggunakan pengembangan R&D menurut Borg & Gall. Tahapan dalam penelitian ini meliputi: 1) potensi dan masalah, 2) pengumpulan data, 3) desain produk, 4) validasi produk, 5) revisi produk, 6) uji coba produk, 7) revisi produk, 8) uji coba pemakaian 9) revisi produk. Instrumen pengumpul data yang digunakan berupa pedoman wawancara, instrumen validasi, dan angket siswa. Jenis data berupa data kuantitatif diperoleh dari hasil angket validator materi, media, pengguna/guru, dan peserta didik. Data kualitatif diperoleh dari saran dan masukan baik dari ahli, pengguna maupun peserta didik. Teknik analisis validator menggunakan Skala Likert. Sedangkan data yang diperoleh dari uji coba produk dan uji coba pemakaian menggunakan skala Guttman. Hasil validasi materi 100% (sangat valid), validasi media 93,75% (sangat valid), validasi pengguna 100% (sangat valid), dan uji coba produk 98,8% (sangat praktis/menarik). Sehingga dapat disimpulkan media pembelajaran berbantuan capcut dinyatakan sangat valid, praktis, menarik dan efektif digunakan dalam pembelajaran tema 2 subtema 1 pembelajaran 6.